Youth Politics: The Political Role of AZANYU in the Struggle for Liberation: The Case of AZANYU Thembisa branch, 1980s to 1996. - Moloi, Tshepo Cyril (My University, 2006)
The overriding theme of this research report is ‘youth politics’ in South Africa in the 1980s and early 1990s. The report explores the role played by the Africanist youth organization, the Azanian National Youth Unity (AZANYU), in the struggle for liberation. It further examines its response to the transition period which took place in the country in the early 1990s. The report explores in particular the role played by the AZANYU Tembisa branch in the struggle. It contends that this branch adopted a militaristic approach in its fight for liberation. And this prohibited it from participating in the local politics mounted by the Tembisa residents. Instead it focused on national politics. The report further illustrates how youth politics were introduced and sustained in Tembisa over a period of time from the early 1970s.
Student Number : 9809033F - MA research report - School of Social Sciences and Humanities - Faculty of Humanities
Keywords: youth politics; South Africa; 1980; 1990; Africanist youth; Azanian National Youth Unity; AZANYU; liberation